Tractive performance prediction for wheeled unmanned vehicles based on dynamics and discrete element method. (May 2021) - Wang, Wen-Hao; Xu, Xiao-Jun; Xu, Hai-Jun; Wang, Li-Ya
Tractive performance is a key factor affecting the field mobility of unmanned vehicles. Presently, studies on the tractive performance of unmanned vehicles mainly focus on the tractive performance of a single wheel, but few studies have used the discrete element method to predict the tractive performance of vehicles. In this paper, a method based on dynamics and discrete elements is proposed to predict the traction performance of a vehicle. Based on the proposed method, the tractive performance of an unmanned vehicle in various field environments is obtained. Firstly, a numerical method for calculating the dynamic tractive performance of the vehicle on a flat road surface is proposed based on vehicle dynamics theory and terramechanics. According to the corresponding soil parameters, the tractive performance of the vehicle on three different sandy loams and three different clays is calculated. The mechanism of action between the wheels and the soil on sloped road is different from that on flat road, and the numerical calculation method is no longer suitable for predicting the tractive performance of vehicles on sloped roads. To predict the tractive performance of unmanned vehicles on various slope roads, the dynamic and discrete element method was used to simulate a sandy loam flat road, sandy loam pitch slope, sandy loam roll slope, light clay flat road, light clay pitch slope, and light clay roll slope. The vehicle dynamics model was established using dynamics software, and the tractive performance of the vehicle on six different roads was obtained through the coupling simulation of dynamics and discrete elements.